(untitled) (Journal of the College of Basic Education, 2026)
Linguistically, the term women (Arabic: “al-nisāʾ”) is the plural of woman (“imraʾah”). The word al-nisāʾ is derived from the root nasāʾa, meaning delay or postponement, and it later came to denote women in general. Terminologically, it refers to the female among the descendants of Adam who has reached the stage of maturity. The word righteousness (ṣalāḥ) linguistically stands as the opposite of corruption (ṭalāḥ), signifying the soundness and uprightness of one’s condition. In terminology, its meaning does not differ from its linguistic sense, as it denotes moral rectitude and the avoidance of evil. As for the status of women, Islam has honored and safeguarded women’s dignity after they had long been oppressed and deprived of their rights. Islam established piety (taqwā) as the sole criterion for superiority between men and women. The woman’s role complements that of the man in building a righteous Muslim family. She is the first school in shaping the child’s character and behavior, preparing a virtuous generation that carries the message of Islam. In this research, I have highlighted illustrious examples of righteous women in the Qur’an, such as Asiyah, the wife of Pharaoh, Maryam (Mary), the daughter of ʿImrān, and Khadījah bint Khuwaylid (may Allah be pleased with them). I have also shed light on their noble educational and moral stances, as they serve as exemplary models for Muslim women across generations.